Project-Based Learning: Promoting Student's Engagement in EFL Classroom - Nurul Namira Simatupang; Fazri Nur Yusuf (International Journal of English and Applied Linguistics (IJEAL), 2024)
The students’ engagement has increasingly become a spotlight in learning, especially in learning English. There are two essential components in engagement which are cognitive and behavioral, which are investments to achieve success in learning. However, the students’ disengagement in EFL classrooms has become a concern in various countries. Therefore, this research was conducted to determine how implementing another learning method, project-based learning, can promote students’ engagement. The writer conducted qualitative research in a senior high school in Medan involving one teacher and students in grade 11. the writer conducted observation and interview. The results from the data obtained concluded that the six steps of project-based learning promoted the students’ engagement, including cognitive and behavioral engagement. This current study contributes to giving the teachers an additional strategy for promoting the students’ engagement using project-based learning. These findings suggest further development related to focusing on various students’ engagement, including cognitive, emotional, and behavioral, to increase the learning outcomes in other schools.